Surface‐Casting Synthesis of Mesoporous Zirconia with a CMK‐5‐Like Structure and High Surface Area. (11th July 2017) - Gu, Dong; Schmidt, Wolfgang; Pichler, Christian M.; Bongard, Hans‐Josef; Spliethoff, Bernd; Asahina, Shunsuke; Cao, Zhengwen; Terasaki, Osamu; Schüth, Ferdi
Abstract: About 15 years ago, the Ryoo group described the synthesis of CMK‐5, a material consisting of a hexagonal arrangement of carbon nanotubes. Extension of the surface casting synthesis to oxide compositions, however, was not possible so far, in spite of many attempts. Here it is demonstrated, that crystalline mesoporous hollow zirconia materials with very high surface areas up to 400 m 2 g −1, and in selected cases in the form of CMK‐5‐like, are indeed accessible via such a surface casting process. The key for the successful synthesis is an increased interaction between the silica hard template surface and the zirconia precursor species by using silanol group‐rich mesoporous silica as a hard template. The surface areas of the obtained zirconias exceed those of conventionally hard‐templated ones by a factor of two to three. The surface casting process seems to be applicable also to other oxide materials.